Reverse distal femoral locking plate for subtrochanter femur fracture (Medical Journal of Indonesia, 2018)
In these case series, we used titanium locking compression plate-distal femur (LCP-DF) plate (Synthes) 9–11 hole using less invasive stabilization system or open reduction technique. This case series aims to determine the functional scores on reverse distal femoral locking plate for subtrochanteric femur fracture. A 34-year-old male with closed subtrochanteric fracture of the right femur (Seinsheimer 2B) with Harris hip scores (HHS) of 17, 96, and 97 obtained consecutively in 0, 6, and 12 months, respectively. A 24-year-old male with closed comminuted subtrochanteric fracture of the right femur (Seinsheimer V) with HHS of 13, 93, and 97 at 0, 6, and 12 months respectively. A 39-year-old male with non-union, left subtrochanteric femur fracture (Seinsheimer 2C) yielded HHS of 38, 73, and 77 at 0, 6, and 12 months, respectively. A 35-year-old female with close subtrochanteric fracture of the right femur (Seinsheimer IIB) yielded HHS of 23, 40, and 73 at 0, 6, and 12 months, respectively. Mean initial HHS and scores at 6 and 12 months reached 22, 75, and 86, respectively.